Scintillation properties of (GaxAl1−x)2O3 ceramics. (July 2023) - Makowski, Michał; Witkowski, Marcin E.; Drozdowski, Winicjusz; Zhang, Guangran; Li, Jiao; Wu, Yiquan
Abstract: In this communication scintillation properties of (Ga x Al 1 − x ) 2 O 3 (x = 1, 0.75, 0.5, and 0.2) ceramics are reported. The investigated samples have been fabricated through two-step spark plasma sintering. Their properties have been studied by means of pulse height spectra, scintillation time profiles, radio- and thermoluminescence. Although room temperature scintillation yields of the samples do not exceed 1000 ph/MeV, their scintillation decays appear relatively fast as compared to single crystals. Highlights: (Ga x Al 1 − x ) 2 O 3 ceramics have been grown by a two-step spark plasma sintering method. Scintillation properties have been examined by means of pulse height spec tra and scintillation time profiles. Glow curves have been deconvoluted and trap parameters have been found. Radioluminescence spectra have been presented.